Readiness or Impairment: Cognitive and Linguistic Differences Between Children Who Learn to Read and Those Who Exhibit Difficulties With Reading in Kindergarten Compared to Their Achievements at the End of First Grade - Ne'eman, Ariel; Shaul, Shelley (Frontiers in Psychology, 2021)
Many studies have attempted to identify measures that predict reading abilities (Lonigan & Shanahan, 2009). The results of these studies may be inclined to over-identification of children considered at risk in kindergarten but who achieve parity in reading by the end of first grade. Therefore, the current study sought to analyze the specific cognitive and linguistic predictors of reading accuracy and reading speed separately. Additionally, the study examined if it is possible to use empirically validated measures to distinguish between children who are not ready to learn how to read in kindergarten but manage to acquire reading skills by the end of first grade, and those who continue to exhibit difficulties. The study followed 98 kindergarteners (43 boys and 55 girls) aged 4 years 10 months to six years from three different schools, who were taught how to read in kindergarten. Multiple measures of general cognitive skills, linguistic abilities, and reading abilities were measured at three different points in time: the beginning of kindergarten, the end of kindergarten, and the end of first grade. The study found that most of the children with good literacy and cognitive abilities learned how to read by the end of kindergarten. The analysis revealed a significant difference in cognitive abilities, such as executive functions and memory, which distinguished between the ability to acquire fluent reading and accurate reading. The study was able to successfully distinguish between “children with difficulties” and “un-ready” children. These results have various implications, especially in regard to the identification of and intervention with kindergarten children at risk for reading disabilities.